PROFIL PEMAHAMAN KONSEP SISWA PADA MATERI ASAM BASA BERDASARKAN TES DIAGNOSTIK TWO TIER MULTIPLE CHOICE DI SMAN 7 PADANG - Suci Wulandari Ismansyar; Dwi Finna Syolendra (STKIP Subang, 2026)
Acids and bases are a topic in chemistry that students often find difficult to understand because it combines conceptual understanding with mathematical calculations. This study aims to describe students’ conceptual understanding profiles regarding acid base concepts based on the results of a two tier multiple choice diagnostic test. This study employed a quantitative descriptive approach involving 67 twelfth-grade students in Phase F at SMAN 7 Padang, distributed across two classes and selected using simple random sampling. Data were collected using a two tier multiple choice diagnostic test consisting of 20 items. Students’ responses were categorized into four groups Correct-Correct (CC/conceptual understanding), Correct-Wrong (CW/misconception error 1/MK-1), Wrong-Correct (WC/misconception error 2/MK-2), and Wrong-Wrong (WW/does not understand the concept), and were then analyzed descriptively in terms of percentages at the overall level, by indicator, and by test item. The results of the study showed that, overall, students achieved a CC percentage of 46.72%, a CW percentage of 25.07%, a WC percentage of 10.30%, and a WW percentage of 17.91%. The highest level of conceptual understanding was found in test items regarding statements consistent with the Arrhenius acid base theory, the limitations of the Arrhenius acid base theory, and the determination of acid base solutions based on litmus paper data, with a CC percentage of 79.10%. The lowest level of understanding was found in the item testing the calculation of the degree of ionization based on pH and Ka, with a percentage of students who answered correctly (CC) of 5.97%. These findings indicate that students relatively well understand the theoretical foundations and identification of acids and bases, but experience significant difficulties when conceptual understanding must be integrated with computational skills, exhibiting a variety of misconceptions.